PENGARUH PERPUTARAN MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT ULTRA JAYA MILK INDUSTRY & TRADING COMPANY TBK PERIODE 2013-2023 - Ineke Kusumawati; Nurwita Nurwita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of working capital turnover and accounts receivable turnover on profitability at PT Ultra Jaya Milk Indistri & Trading Company Tbk for the 2013-2023 period. This research method used is a quantitative research method. The data used is secondary data in the form of financial reports of PT Ultra Jaya Milk Indistri & Trading Company Tbk for the 2013-2023 period. The analytical method used is descriptive analysis, classical assumption test, correlation coefficient, coefficient of determination, multiple linear regression analysis, and hypothesis testing with t test and F test using SPSS version 27. Partial research results show that working capital turnover has a value of t < ttable or │-1,840│ < 2.306 with a significance level of 0.103 > 0.05 so that it partially has no significant effect on profitability as proxied by ROA. Receivables turnover has a value of tcount < ttable or 0.379 < 2.306 with a significant level of 0.715 > 0.05, but partially it has no significant effect on profitability as proxied by ROA. Simultaneous research results between working capital turnover and receivables turnover on profitability as proxied by ROA show the value of Fcount < Ftable or 2.371 < 4.460 with a significant level of 0.155 > 0.05. Simultaneously working capital turnover and receivables turnover do not have a significant effect on profitability as proxied by ROA. Meanwhile, the coefficient of determination value is 21.5%, which means that the independent variables consisting of working capital turnover and accounts receivable turnover do not have a significant effect on profitability as proxied by ROA, while the remaining 78.5% is influenced by other variables not examined in this research.